Prevalencia de trastornos temporomandibulares mediante el índice anamnésico simplificado de Fonseca en estudiantes de odontología de la Universidad Juárez del Estado de Durango, México - Solís-Martínez, Luis Javier (2021)
Objective: The objective was to estimate the prevalence of temporomandibular disorders (TMD), in students of the Faculty of Dentistry. Material and Methods: This was a descriptive, observational, prospective, cross-sectional study. The study included 18 to 28-year-old students from the Faculty of Dentistry of the Universidad Juárez del Estado de Durango, México, attending the 1st to 8th semester of the 2018-A school year in whom the simplified Fonseca anamnestic index (sFAI) was applied to characterize TMD. The sample size was determined using the Epi InfoTM software, obtaining a total sample size of 263 individuals. The R Studio (2019) statistical package was used to describe the data. Results: The prevalence of TMD in the study population was 63%, with a mild disorder being the most prevalent in 44%. The Chi2 test showed statistically significant differences between sex and TMD (p = 0.001) and between sex and 5 items of the sFAI: item 4 (p= 0.001), item 7 (p= 0.001), item 8 (p = 0.021), item 9 (p= 0.001) and item 10 (p = 0.001). Conclusions: There is a high prevalence of TMD in the student population of the Faculty of Dentistry of the Universidad Juárez del Estado de Durango, Mexico, with females presenting a higher prevalence of the presence and manifestation of symptoms in these disorders.